LINGUISTIC PERSONALITY OF METROPOLITAN ANTHONY OF SOUROZH (BLOOM) - Svitlana Shepitko; Mariia Smyrnova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The paper focuses on the essential problem of linguistic personality analysis. It aims to study language means representing linguistic personality of Metropolitan Antony of Sourozh (Bloom). The authors analyse the linguistic personality at three levels: semantic, linguo-cognitive and motivational. The linguistic personality is characterised through the prism of linguistic consciousness and speech behaviour, i.e. from the perspective of linguistic conceptology and the theory of discourse. The research results show that the linguistic personality's cornerstone is the concept "BELIEF" which is interpreted by various confessions differently. The metropolitan mainly uses questions which can occur in the quotes used during a sermon that transfers a listener to a format of a polilologue. The preacher most often addresses the tactics of conducting a dialogue and the tactics of "thought-reading". As a preacher, Metropolitan Anthony of Surozh is a representative of Orthodox Church as a social institute, whose picture of the world is also influenced by the national picture of the world which reflects religious, historical, cultural and political presuppositions ofEnglandas well as those of 20th centuryWestern Europe. The authors state that the linguistic personality of a preacher experiences transformations under the pressure of secular society reflected at the verbal and semantic levels and, depending on a sermon recipient's type of personality - at the motivation level.